2021
DOI: 10.4209/aaqr.200545
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Air Pollutant Concentrations and the Impact of Meteorology in Shandong Province, Coastal China, during 2013-2019

Abstract: Emissions of air pollutants have been reduced in Shandong Province of China during 2013-2019. Meteorological conditions are an important factor affecting air pollutant concentrations, but few quantitative studies have been conducted on the effects of long-term and seasonal changes in meteorological on air quality. In this study, the trends in six criteria pollutants (including SO2, CO, PM10, PM2.5, NO2, and O3) from 2013 to 2019 in Shandong Province were analysed (PM2.5 and PM10: particulate matter with aerody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The modal aerosol dynamics model for Europe (MADE/SORGAM) was used to calculate the aerosol chemistry. The initial and lateral meteorological boundary conditions for WRF/Chem were generated from the National Centre for Environmental Prediction (NCEP) Final Analysis (FNL) data, which were available at a 1 • × 1 • resolution and temporal resolution of 6 h. Our previous work contains more detailed descriptions of WRF/Chem (Chen et al, 2018;Wang et al, 2021;Zhao et al, 2021b). A two-level nested-grid architecture was employed for implementation of the WRF/Chem modeling system (Fig.…”
Section: Modeling System 221 Model Selection and Parameter Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modal aerosol dynamics model for Europe (MADE/SORGAM) was used to calculate the aerosol chemistry. The initial and lateral meteorological boundary conditions for WRF/Chem were generated from the National Centre for Environmental Prediction (NCEP) Final Analysis (FNL) data, which were available at a 1 • × 1 • resolution and temporal resolution of 6 h. Our previous work contains more detailed descriptions of WRF/Chem (Chen et al, 2018;Wang et al, 2021;Zhao et al, 2021b). A two-level nested-grid architecture was employed for implementation of the WRF/Chem modeling system (Fig.…”
Section: Modeling System 221 Model Selection and Parameter Settingsmentioning
confidence: 99%
“…Zhang et al (2019) reported that meteorological conditions played an important role in decreasing winter PM 2.5 concentrations in the Yangtze River Delta (YRD) and the Beijing-Tianjin-Hebei (BTH) regions. Our previous study found that the inter-annual meteorological changes contributed 3.4%-18.6% to reductions in PM 2.5 , PM 10 , SO 2 , CO, and NO 2 concentrations in Shandong province from 2015 to 2019; however, these changes had little impact on O 3 when compared with 2013 levels (Zhao et al, 2021b). In addition, severe air pollution events with daily PM 2.5 concentrations >200 μg/m 3 occurred during the COVID-19 outbreak due to unfavorable meteorological conditions; however, anthropogenic emissions decreased (Li et al, 2021;Wang et al, 2020b;Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…48,57 However, the correlation coefficient shows that PM10 (P = 0.118, 2020) has a more signicant correlation with precipitation than PM2.5 (P = 0.059, 2020), indicating that raindrops have a stronger scouring effect on large particulate matter particles and a weaker scouring effect on small particulate matter. 58…”
Section: Effect Of the Meteorological Factor On Air Qualitymentioning
confidence: 99%
“…In 2016, on-road vehicles accounted for about 39% and 20% of total NO2 and CO emissions in the European Union (EU), and it is found those passenger vehicles are the major cause of NO2 and CO emissions from road transportation (Mohd Shafie and Mahmud, 2020;Iqbal et al, 2022). It has been reported that for every kilogram of gasoline burned by the automobile engine (Deng, 2006;Zhao et al, 2021), 15 kilograms of fresh air will be consumed, and 150-200 grams of carbon monoxide, 4-8 grams of hydrocarbons, 4-20 grams of nitrogen oxide and other pollutants will be emitted at the same time. The harmful exhaust gas emitted by a car in a year was three times larger than its own weight.…”
Section: Introductionmentioning
confidence: 99%